Efficient and Easy Conversion of Human iPSCs into Functional Induced Microglia-like Cells - Lanfer, Jonas; Winner, Beate; Kaindl, Johanna; Krumm, Laura; Acera, Miguel Gonzalez; Neurath, Markus; Regensburger, Martin; Krach, Florian (International Journal of Molecular Sciences, 2022)
Current protocols converting human induced pluripotent stem cells (iPSCs) into induced microglia-like cells (iMGL) are either dependent on overexpression of transcription factors or require substantial experience in stem-cell technologies. Here, we developed an easy-to-use two-step protocol to convert iPSCs into functional iMGL via: (1) highly efficient differentiation of hematopoietic progenitor cells (HPCs) from iPSCs, and (2) optimized maturation of HPCs to iMGL. A sequential harvesting approach led to an increased HPC yield. The protocol implemented a freezing step, thus allowing HPC biobanking and flexible timing of differentiation into iMGL. Our iMGL responded adequately to the inflammatory stimuli LPS, and iMGL RNAseq analysis matched those of other frequently used protocols. Comparing three different coating modalities, we increased the iMGL yield by culturing on uncoated glass surfaces, thereby retaining differentiation efficiency and functional hallmarks of iMGL. In summary, we provide a high-quality, easy-to-use protocol, rendering generation and functional studies on iMGL an accessible lab resource.
CRIS-Team Scopus Importer:2022-04-29
Keywords: cell differentiation; immunology; microglia; neurology; pluripotent stem cells